Епиграфска сведочанства о Јулијановом проласку кроз Илирик 361. године (Three Comments on Late Antiquity History) - Milin, Milena (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Апстракт: 1. Предлаже се ново читање CIL III 4002 rr. 3-7. Натпис се датује у другу пол. 4. в, према христограму, карактеристичном за овај период. 2.Одбацује се важећа емендација рукописног (Amm. Marc. 31,15,6) diristianum u christianum и предлаже се читање dirist<r>anum = durostorianum, према варијанти топонима Durostorum, Dri$stra, забележеном у том облику код Зонаре, XVI 12.3. Коментарише се израз Ecclesia catholica у Пасији св. Иренеја и Ecclesia у спису Altercatio Heracliani laici cum Germinio episcopo. THREE COMMENTS ON LATE ANTIQUITY HISTORY Summary 1. An Early Christian Pannonian Epitaph The author suggests corrections in reading the inscription CIL III 4002, lines 3-7 (see pp. 1-2). The formula q(ui vixit ) ann(os) , lines 3-4, was common in Late Antiquity, unlike the previous reading...ann(orum),which was typical for the Early Empire. L.5 memoria frequently appeared in funerary monuments in Late Antiquity. L. 6 Instead of unlikely collegae, the complement colloc(avit or –erunt) has been suggested, according to analogies sedem conlocasse (Siscia, CIL 3996) sepulcrum (!) collocavit, with the Christogram ( Siscia ,CIL 3996a). The inscription can be more precisely dated with regard to the Christogram. In nearby Sirmium, this symbol repeatedly appears in epitaphs, whether unaccompanied, or between the letters a and w . According to a dated inscription with a Christogram from Constantius times, the entire group of inscriptions bearing this symbol may be supposed to have originated from mid-, or, at the latest, second half of 4th century (notes 2-4). 2. Durostoranus (Amm. Marc. XXXI 15, 6 ) In the paragraph referred to above: Verum introire non ausus, qui missus est, per Christianum quendam portatis scriptis et recitatis, utque decebat, contemptatis parandis operibus dies et nox omnis absumpta (ed. W.Seyfarth, Leipzig 1978), the author, instead of the reading to date, christianum, suggests the restitution of the Codex lection Vat. lat. 1873 dirist<r>anum, which would be the adjective derived from the toponym D(i)ristra,a variant of Durostorus, cf. Zonara (XVI 12 ) e/n Dorosto$lw...toy#to d h% Dri$stra e/sti. Further on, ( ...scriptis et recitatis, utque dicebat, contemptatis , parandis operibus dies et nox omnis absumpta), two differently noted or emendated points are present. The one is ut dicebat, in a later manuscript, and in Seyfarth’s critical edition, changed into ut decebat. This emendation is not necessary: the emissary said that he had taken the letter and given the message that was ignored by the inhabitans, and not “given the message as was befitting”. That would, therefore, mean that between the other two options, contemptatis(=contemptis, cf. note 13) and contemplatis, the former should be decided on. 3. On terms Ecclesia and catholica in Early Christian texts from Sirmium The term Ecclesia catholica is found at the end of Passion of St. Irenaeus (executed in AD 304), in his prayer (cf. above, p. 6, with note 15). The syntagma indicates rather that the Passion originates from the era of struggle against heresies (second half of 4th century), when it was necessary to emphasize that Irenaeus was a member of Orthodox Church, than that it dates from the first third of the century, when the discussed syntagma stood for a united, universal, ecumenical Church (note 19). This is concurrent with the absence of ecclesia catholica in Passions of other Sirmium martyrs, on epigraphic monuments, (note 16) and in Altercatio- debate, conducted in January 366, between Semi-Arian Bishop Germinius and layman Heraclianus (note 17).